High‐resolution imaging for the detection and characterisation of circulating tumour cells from patients with oesophageal, hepatocellular, thyroid and ovarian cancers. Issue 1 (19th August 2015) - Dent, Barry M.; Ogle, Laura F.; O'Donnell, Rachel L.; Hayes, Nicholas; Malik, Ujjal; Curtin, Nicola J.; Boddy, Alan V.; Plummer, E. Ruth; Edmondson, Richard J.; Reeves, Helen L.; May, Felicity E.B.; Jamieson, David
<x xml:space="preserve">Abstract</x> Interest has increased in the potential role of circulating tumour cells in cancer management. Most cell‐based studies have been designed to determine the number of circulating tumour cells in a given volume of blood. Ability to understand the biology of the cancer cells would increase the clinical potential. The purpose of this study was to develop and validate a novel, widely applicable method for detection and characterisation of circulating tumour cells. Cells were imaged with an ImageStreamX imaging flow cytometer which allows detection of expression of multiple biomarkers on each cell and produces high‐resolution images. Depletion of haematopoietic cells was by red cell lysis, leukocyte common antigen CD45 depletion and differential centrifugation. Expression of epithelial cell adhesion molecule, cytokeratins, tumour‐type‐specific biomarkers and CD45 was detected by immunofluorescence. Nuclei were identified with DAPI or DRAQ5 and brightfield images of cells were collected. The method is notable for the dearth of cell damage, recoveries greater than 50%, speed and absence of reliance on the expression of a single biomarker by the tumour cells. The high‐quality images obtained ensure confidence in the specificity of the method. Validation of the methodology on samples from patients with oesophageal, hepatocellular, thyroid and ovarian cancers confirms its utility and specificity. Importantly, this adaptable method is applicable to all tumour types including those of nonepithelial origin. The ability to measure simultaneously the expression of multiple biomarkers will facilitate analysis of the cancer cell biology of individual circulating tumour cells.